Does Antigen Glycosylation Impact the HIV-Specific T Cell Immunity? - Olvera, Alex; Cedeño, Samandhy; Llano, Anuska; Mothe, Beatriz; Sanchez, Jorge; Arsequell, Gemma; Brander, Christian (Frontiers in Immunology, 2021)
It is largely unknown how post-translational protein modifications, including glycosylation, impacts recognition of self and non-self T cell epitopes presented by HLA molecules. Data in the literature indicate that O- and N-linked glycosylation can survive epitope processing and influence antigen presentation and T cell recognition. In this perspective, we hypothesize that glycosylation of viral proteins and processed epitopes contribute to the T cell response to HIV. Although there is some evidence for T cell responses to glycosylated epitopes (glyco-epitopes) during viral infections in the literature, this aspect has been largely neglected for HIV. To explore the role of glyco-epitope specific T cell responses in HIV infection we conducted in silico and ex vivo immune studies in individuals with chronic HIV infection. We found that in silico viral protein segments with potentially glycosylable epitopes were less frequently targeted by T cells. Ex vivo synthetically added glycosylation moieties generally masked T cell recognition of HIV derived peptides. Nonetheless, in some cases, addition of simple glycosylation moieties produced neo-epitopes that were recognized by T cells from HIV infected individuals. Herein we discuss the potential importance of these observations and compare limitations of the employed technology with new methodologies that may have the potential to provide a more accurate assessment of glyco-epitope specific T cell immunity. Overall, this perspective is aimed to support future research on T cells recognizing glycosylated epitopes in order to expand our understanding on how glycosylation of viral proteins could alter host T cell immunity against viral infections.